2004
DOI: 10.1074/jbc.m312389200
|View full text |Cite
|
Sign up to set email alerts
|

NEDL1, a Novel Ubiquitin-protein Isopeptide Ligase for Dishevelled-1, Targets Mutant Superoxide Dismutase-1

Abstract: Approximately 20% of familial amyotrophic lateral sclerosis (FALS) arises from germ-line mutations in the superoxide dismutase-1 (SOD1) gene. However, the molecular mechanisms underlying the process have been elusive. Here, we show that a neuronal homologous to E6AP carboxyl terminus (HECT)-type ubiquitin-protein isopeptide ligase (NEDL1) physically binds translocon-associated protein-␦ and also binds and ubiquitinates mutant (but not wild-type) SOD1 proportionately to the disease severity caused by that parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
147
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(151 citation statements)
references
References 45 publications
2
147
1
1
Order By: Relevance
“…Furthermore, it has been reported that NEDL1 interacts with p53 and enhances transcriptional activity of p53 and p53-mediated apoptotic cell death. These findings suggest that NEDL1 regulates cell proliferation and differentiation, stress responses, and DNA-damage responses [15,16].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, it has been reported that NEDL1 interacts with p53 and enhances transcriptional activity of p53 and p53-mediated apoptotic cell death. These findings suggest that NEDL1 regulates cell proliferation and differentiation, stress responses, and DNA-damage responses [15,16].…”
Section: Introductionmentioning
confidence: 79%
“…A novel HECT-type E3 ubiquitin ligase, NEDL1, has been reported to be expressed in neuronal tissues including the spinal cord and to selectively bind to and ubiquitinate mutant (but not wild-type) SOD1 and Dvl1 [15]. Furthermore, it has been reported that NEDL1 interacts with p53 and enhances transcriptional activity of p53 and p53-mediated apoptotic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were observed for HECW1. HECW1 (NEDL1) has been shown to be an E3 ligase for Dvl-1 (Miyazaki et al, 2004) and to cooperate with p53 to induce apoptosis independent of its E3 ligase activity (Li et al, 2008a). Thus, WWP1, Itch and HECW1 additively suppress the ErbB4 expression in some breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…This is activated when cells are exposed to hostile conditions such as oxidative stress, viral infection and glucose deprivation (Kunst et al, 1997;Miyazaki et al, 2004;Nagasawa et al, 2007). Inhibition of TRAP complex function by depletion of the Trap-g subunit might influence not only efficient protein translocation but also the UPR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the TRAP complex induced by the unfolded protein response (UPR) pathway might discriminate ER-associated degradation substrates from correctly folded substrates, which results in accelerating degradation (Nagasawa et al, 2007). One of the four TRAP subunits, Trap d also binds misfolded dismutase-1 superoxide, but not the wild-type form, with the ubiquitin-protein isopeptide ligase and this forms an ubiquitinated protein complex (Kunst et al, 1997;Miyazaki et al, 2004). Therefore, the TRAP complex might be involved in the UPR pathway to maintain cellular homeostasis when cells are exposed to unfavorable conditions, such as oxidative stress, viral infections, and glucose deprivation.…”
Section: Introductionmentioning
confidence: 99%